Leadership in crisis: the lived experiences of seven school leaders during COVID-19 - Asqueri, Emily, author; Cooner, Donna, advisor; Frederiksen, Heidi, committee member; Barnes, Wendy, committee member; O'Donnell-Allen, Cindy, committee member (Colorado State University. Libraries, 2023)
This study, grounded in a constructivist view of phenomenology, explores the lived experiences of school leaders during the COVID-19 pandemic. The research identifies several implications for practice, including the need to re-evaluate teacher and administrator licensure programs, with a focus on providing opportunities for educators to gain practical experience in navigating crises. Additionally, professional development courses should be tailored to address educators' specific deficits and strengths, fostering better leadership. Addressing inequities in education, particularly regarding food security and the digital divide, remains critical. Furthermore, the study highlights the importance of allocating resources to mental health and self-care initiatives, not only for school leaders but also for staff, students, and the community, while actively working to destigmatize mental health. Finally, this research underscores the need to refocus on the primary purpose of education, which is to meet the needs of students, rather than becoming mired in divisive debates. Recommendations for future research include conducting interviews with a more diverse group of school leaders to capture a broader range of experiences. Additionally, long-term studies may be necessary to understand the lasting effects of leadership decisions during the pandemic. In conclusion, this research calls for collective action to address systemic inequities in education. It acknowledges the complexity of these challenges and urges stakeholders to support educators and students. In the interim, school leaders, licensure programs, and professional development courses must prioritize the development of leaders who can effectively navigate uncertainty and crises, thereby benefiting the entire educational community.
Keywords: crisis leadership; phenomenology; school leader; education; COVID-19; school administrator